2020
DOI: 10.1002/bjs.11471
|View full text |Cite
|
Sign up to set email alerts
|

Colonic transit in patients after anterior resection: prospective, comparative study using single-photon emission CT/CT scintigraphy

Abstract: Background Bowel dysfunction after anterior resection is well documented, but its pathophysiology remains poorly understood. No study has assessed whether postoperative variation in colonic transit contributes to symptoms. This study measured colonic transit using planar scintigraphy and single‐photon emission CT (SPECT)/CT in patients after anterior resection, stratified according to postoperative bowel function. Methods Symptoms were assessed using the low anterior resection syndrome (LARS) score. Following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Mochiki et al found that, while a 300‐kcal meal did not induce contractions in healthy controls, patients with increased stool frequency had relative hypermotility proximal to the anastomosis compared to those with normal stool frequency, suggesting an increased gastrocolic reflex [15]. More recently, patients with major LARS have been shown to have increased colonic transit compared to patients with no‐LARS [16]. Patients with major LARS have also been shown to have a significant increase in post‐prandial neorectal pressure compared to patients without LARS after total mesorectal excision [17].…”
Section: Discussionmentioning
confidence: 99%
“…Mochiki et al found that, while a 300‐kcal meal did not induce contractions in healthy controls, patients with increased stool frequency had relative hypermotility proximal to the anastomosis compared to those with normal stool frequency, suggesting an increased gastrocolic reflex [15]. More recently, patients with major LARS have been shown to have increased colonic transit compared to patients with no‐LARS [16]. Patients with major LARS have also been shown to have a significant increase in post‐prandial neorectal pressure compared to patients without LARS after total mesorectal excision [17].…”
Section: Discussionmentioning
confidence: 99%
“…In an anorectal physiology study, 23 patients with major LARS had a hyperactive postprandial response with a significant increase in postprandial neorectal pressure compared to patients without LARS (n = 9) after total mesorectal excision (85). More recently, colonic transit studies have demonstrated that patients with major LARS have significantly faster transit compared to those with minor or no LARS (26). Increased transit could be a consequence of either hypofunction of the rectosigmoid brake, or overactivity of proximal propulsive activity, further supporting the role of altered colonic motility in LARS.…”
Section: Colonic Motility After Anterior Resectionmentioning
confidence: 99%
“…While anorectal factors have been extensively researched with regards to their role in LARS (17,(21)(22)(23)(24), less is known about the role of colonic physiology in the aetiology of LARS. Research has continued to emerge that significant alterations in colonic motility are present in LARS, likely demonstrating an underappreciated pathophysiological mechanism (25,26). This review will focus on this important role of colonic motility and its implications in LARS.…”
Section: Introductionmentioning
confidence: 99%
“…There are increasing data from different modalities on changes seen in patient with major LARS including the use of SPECT, multimodal rectal stimulation, anorectal physiology tests and HRM [4,5].…”
Section: Altered Colonic Motility Is Associated With Low Anterior Resmentioning
confidence: 99%
“…There are increasing data from different modalities on changes seen in patient with major LARS including the use of SPECT, multimodal rectal stimulation, anorectal physiology tests and HRM [4,5]. The challenge will be to understand how to combine the data from these approaches to better understand the complex pathophysiology underlying LARS and develop improved therapeutic approaches but also preventative strategies.…”
mentioning
confidence: 99%